Accuracy of pulmonary ultrasound versus chest radiography for detecting pulmonary congestion resulting from increased pulmonary blood flow in children with congenital heart disease and left-to-right shunting - de Carvalho, Haroldo Teófilo [UNESP]; Bonatto, Rossano César [UNESP]; Campos, Fábio Joly [UNESP]; Martin, Joelma Gonçalves [UNESP]; Fioretto, José Roberto [UNESP] (Elsevier, 2022)
Introduction: Congenital heart diseases are a set of simple or complex dynamic heterogeneous malformations that originate in the embryo, progress through the pregnancy, and considerably change throughout the course of extrauterine life. They are the most common congenital defect, with a global prevalence estimated at 1.8 cases per 100 live births. These diseases can be classified by the cardiovascular segment affected and the impact on blood oxygenation and pulmonary flow. One of their most feared repercussions is pulmonary hypertension, which can result from lung exposure to increased blood flow, which changes vascular tone and causes medial hypertrophy and vascular remodeling. The advent of echocardiography has revolutionized healthcare for these children; however, chest radiography is still the most commonly used method for detecting increased blood flow and pulmonary edema. Objectives: Thus, this study compared the accuracy of ultrasound and chest radiography in detecting congestion resulting from increased pulmonary blood flow in children with congenital heart disease and left-to-right shunting. Methods: This is an observational longitudinal analytical prospective study comparing lung ultrasounds and chest radiographs of patients with congenital heart disease. Results: Our results suggest that ultrasound, which is a noninvasive diagnostic method that emits no radiation, has a discriminatory capacity similar to that of radiography, and has 92.59 % accuracy, 89.47 % sensitivity, and 100 % specificity. Conclusions: Pulmonary ultrasound is highly accurate, sensitive, and specific, and can be used to assess pulmonary congestion and edema resulting from increased blood flow in patients with heart disease.
Keywords: Congenital cardiomyopathy; Increased pulmonary flow; Pediatrics; Ultrasound